Legal Review of Business Registration and Verification Service Mechanisms in Timor-Leste (SERVE, IP/Serviço De Registo E Verificação Empresarial, Instituto Publico) - Cristovão Pinto, Felix; Mashdurohatun, Anis (Jurnal Hukum Khaira Ummah, 2025)
This research aims to examine juridically and analytically the mechanism of business registration and verification services in Timor-Leste, which is carried out by the Serviço de Registo e Verificação Empresarial, Instituto Público (SERVE, IP) as a public institution responsible for the legalization process of business entities. The focus of the study is directed at the legal basis underlying the operation of SERVE, IP., the procedures of business registration and verification services, as well as the challenges faced in the implementation of government policies in the field of economic licensing. The research method used is normative juridical with a descriptive-analytical approach, through a literature review of regulatory analysis and relevant legislation, as well as official documentation from the Government of Timor-Leste. The approach method employed in the preparation of this thesis is normative juridical research (normative legal research). Normative juridical research is library-based legal research conducted by examining library materials or secondary data only. The results of the study show that the existence of SERVE, IP., has made a significant contribution to government efforts in creating legal certainty, transparency, and efficiency for entrepreneurs in Timor-Leste. The mechanism applied is relatively simple with the concept of a one-stop shop that facilitates the business registration process. However, its implementation still faces considerable challenges, including limited competent human resources, suboptimal utilization of information technology in the service system, and overlapping sectoral regulations with existing economic licensing laws. These factors affect the speed, effectiveness, and quality of services provided to the public and the private sector. To improve the effectiveness of the mechanism, efforts are needed to harmonize sectoral regulations with national economic licensing policies, strengthen the institutional capacity of SERVE, IP., and develop a more integrated digital service system. Thus, the business registration and verification policy implemented is expected to support private sector growth, improve the investment climate, and reinforce sustainable economic development in Timor-Leste.